LONG WAVES IN RECTANGULAR TANK GENERATED BY PLANE - Victor V. Trepachev (Advanced Engineering Research)
The surface form of heavy liquid in the rectangular wave tank covered with long waves over the flat bottom is i nvestigated. The waves are generated by the horizontal h armonic oscill a tions of the screen - formed wavemaker. The accurate solution to the boundary problem with regard to the energy dissipation in liquid is obtaine d. The results are applicable for the calcul a tion and laboratory simulation of the surface and acou stic waves.